Impact of Cross-Cultural Adaptation and Innovative Self-Efficacy on Innovative Behavior: A Case Study of Chinese Employees in Sino-Thai Joint Ventures - Wang, Bo; Mo, Lingfen; Wang, Xinrui (Journal of China-ASEAN Studies, 2023)
In the contemporary era, innovation has become the core competitive advantage for businesses, with employees’ innovative capabilities directly impacting a company’s innovation potential. The globalization of business operations has led to the international mobility of personnel, posing challenges related to both cross-cultural adaptation and innovation for expatriate employees. This study primarily employing quantitative research methods, focuses on employees in Chinese companies in Thailand and investigates the relationship between cross-cultural adaptation and innovation behavior, as well as the role of innovation self-efficacy. A random sampling method and utilizing an online questionnaire collection system were used and a total of 205 valid responses were received. The research findings reveal that crosscultural adaptation has a positive impact on both employee innovation behavior and their innovation self-efficacy. Employee innovation self-efficacy positively influences innovation behavior, acting as a mediator between cross-cultural adaptation and innovation behavior. Building upon these findings, this paper presents specific recommendations for enhancing expatriate employees’ cross-cultural adaptation abilities to bolster their innovation capabilities.